Biomimetic dental prostheses designed by artificial intelligence versus CAD software. - Dr Walter Lam; Dr Reinhard Chau (Elsevier, 2023)
Aim or Purpose: This study aimed to compare the biomimetic morphology of single-molar dental prostheses designed by an artificial intelligence (AI) system and by a trained dental technician using commercial dental CAD software programs. Materials and Methods: Dentate participants who fulfilled the selection criteria were recruited, and digital casts of their maxillary arch were scanned as original casts and duplicated as duplicated casts (Ethics approval obtained UW 20-848). The maxillary right first molar was removed on the duplicated casts to simulate tooth loss as prepared casts. AI was then instructed to design the missing maxillary right first molars for the eight prepared casts as an experimental group A. An experienced dental technician was also instructed to perform the same restoration using CAD software as experimental group B. Eight pieces of AI-designed crowns and eight pieces of CAD-designed crowns were best-fit superimposed to corresponding original teeth, respectively, and differences in surface morphology were measured by calculating the Hausdorff distance. Results: The median Hausdorff distance of AI-designed crowns to original teeth was 0.366 mm, while that of CAD-designed crowns was 0.304 mm. Conclusions: AI shows promising results in designing biomimetic crowns. However, additional studies with more training data would be needed to examine this observation further.